# GRAFIK X

Title says it all, I just want to know how khổng lồ factor \$(x+y)^4+x^4+y^4\$. I only know that it"s possible to factor, but got no idea how khổng lồ vị it. If it were a single-variable polynomial I could try to find rational roots or something, but I"m lost with this one.

Bạn đang xem: Grafik x

Beyond what I have sầu posted, it cannot be factored in the real field. If you want to lớn factor it in the complex field, you have sầu lớn learn how to solve sầu a quartic equation because you essentially need lớn know that roots of \$(t+1)^4 + t^4 + 1 = 2t^4 + 4t^3 + 6t^2 + 4t + 2 = 0\$, it can be simplified to lớn \$t^4 + 2t^3 + 3t^2 + 2t + 1 = 0\$.Lucky enough, this is equal khổng lồ \$(t^2 + t + 1)^2\$

Thus \$x^4 + y^4 + (x + y)^4 = (x^2 + xy + y^2)^2\$.No further factorization is available in the real field...

Best wishes

Note that \$\$(x+y)^4 + x^4 + y^4 = y^4 ((x/y+1)^4 + (x/y)^4 + 1)\$\$và see if you can factor \$((t+1)^4 + t^4 + 1\$. There is a quadratic factor.

This is a symmetric polynomial in \$x\$ & \$y\$, hence it can be expressed, by Newton"s theorem, as a polynomial in \$s=x+y\$ và \$p=xy\$.

Indeed \$x^2+y^2=(x+y)^2-2xy=s^2-2p\$, whence\$\$x^4+y^4=(x^2+y^2)^2-2x^2y^2=(s^2-2p)^2-2p^2=s^4-4ps^2+2p^2.\$\$Therefore\$\$(x+y)^4+x^4+y^4=2s^4-4ps^2+2p^2=2(s^2-p)^2=2(x^2+xy+y^2)^2.\$\$

\$x^2+xy+y^2\$ is irreducible in \$ eftekumsk.combf R\$, but factors in \$ eftekumsk.combf C\$ as\$\$(x-jy)(x-j^2y)quad extwhere j;  extvà j^2 ; extare the non-real cubic roots of unity.\$\$

I know that using complex algebra, we can factor \$x^4 + y^4 = (x^2 + y^2 + sqrt2xy)(x^2 + y^2 - sqrt2xy)\$. I have no idea how khổng lồ proceed forward...Good luck

I am sorry, there is a slight mistake, I forgot factoring 2. Thus \$x^4 + y^4 + (x+y)^4 = 2(x^2 + xy + y^2)^2\$

\$\$(x+y)^4+x^4+y^4=(x^2+y^2+2xy)^2+(x^2+y^2)^2-2(xy)^2=\<(x^2+y^2+2xy)^2-(xy)^2>+<(x^2+y^2)^2-(xy)^2>=\(x^2+y^2+xy)(x^2+y^2+3xy)+(x^2+y^2+xy)(x^2+y^2-xy)=\(x^2+y^2+xy)(2x^2+2y^2+2xy)=2(x^2+y^2+xy)^2\$\$

\$\$x^4 + y^4 + (x + y)^4=2 x^4 + 4 x^3 y + 6 x^2 y^2 + 4 x y^3 + 2 y^4\$\$\$\$=x (x (x (2 x + 4 y) + 6 y^2) + 4 y^3) + 2 y^4=2 x^4 + y (4 x^3 + y (6 x^2 + y (4 x + 2 y)))\$\$\$\$=4 y^2 (x^2 + x y) + 2 (x^2 + x y)^2 + 2 y^4=2 (x^4 + 2 x^3 y + 3 x^2 y^2 + 2 x y^3 + y^4)\$\$\$\$=2 (x^2 + x y + y^2)^2\$\$

Thanks for contributing an answer lớn neftekumsk.comematics Staông xã Exchange!

Please be sure to answer the question. Provide details & cốt truyện your research!

But avoid

Asking for help, clarification, or responding to other answers.Making statements based on opinion; baông xã them up with references or personal experience.

Use neftekumsk.comJax khổng lồ format equations. neftekumsk.comJax reference.

To learn more, see our tips on writing great answers.

Post Your Answer Discard

By clicking “Post Your Answer”, you agree khổng lồ our terms of service, privacy policy và cookie policy

## Not the answer you're looking for? Browse other questions tagged factoring or ask your own question.

site design / logo © 2021 Staông chồng Exchange Inc; user contributions licensed under cc by-sa. rev2021.6.29.39606

Your privacy

By clicking “Accept all cookies”, you agree Stack Exchange can store cookies on your device và discthua information in accordance with our Cookie Policy.